Printing paste, pigment printing paste and application of pigment printing paste
By using a composite thickener of alkali swelling thickener and reverse-phase emulsion thickener in printing pastes in the wax printing field, combined with metal salt, the problem of back seepage and pattern clarity in the paint imitation wax printing is difficult to take into account both the back seepage and pattern clarity in the paint imitation wax printing. , achieving efficient printing effect and promoting the promotion of paint imitation wax printing.
Patent Information
- Application Number
- CN202411310821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
AI Technical Summary
In the field of wax printing, the paint imitation wax printing process is difficult to take into account the backskin effect and pattern clarity, resulting in limited promotion and application.
Provide a printing paste, a composite thickener containing alkali swelling thickener and reverse-phase emulsion thickener, combines metal salts to regulate rheological properties and viscosity, improves shear thinning ability and water-bearing properties, and ensures paint printing. The penetration capacity and pattern clarity of color paste during printing.
The back seepage effect and pattern clarity in painted wax prints are achieved, and the promotion and use of painted wax prints are promoted. The resulting printed fabric has the effect of consistent front and back sides, clear patterns, and thick and fluffy feel.
Smart Images

Figure BDA0005053305660000051 
Figure BDA0005053305660000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile printing and dyeing, in particular to a printing paste and a coating printing paste and applications thereof. Background Art
[0002] Wax printing is a dyeing process with a history of 3,000 years. Its unique charm lies in the ice pattern formed by the natural cracking of wax. Now wax-printed fabrics are one of the most widely used printed and dyed fabrics in the African textile market. Its characteristics are consistent front and back, fine and natural wax patterns, bright colors and rugged style. At present, the wax printing industry generally uses imitation wax printing technology to replace traditional wax printing. Imitation wax printing is to directly use the printing method to print products similar to the style of real wax dyeing. Compared with wax printing, the production cycle of imitation wax printing is greatly shortened, the efficiency is greatly improved, the process technology is simple, the production cost is low, and the reproducibility is good. At present, wax-printed fabrics occupy 80% of the global market share. Most manufacturers use rotary screen printing machines to produce pure cotton imitation wax products, and reactive dye printing is the main printing process.
[0003] Compared with reactive printing, paint printing has outstanding low-carbon and emission reduction characteristics. After printing, it only needs one high-temperature setting without steaming and multiple washings, which shortens the process. It is estimated that every 10,000 meters of printing can reduce CO2 emissions by 0.9 tons, so paint imitation wax printing is the development direction of wax printing.
[0004] In the fields of home textiles and clothing, the pigment printing process has been very mature after more than 30 years of development. However, in the field of wax printing, the pigment printing process has been considered by industry experts to be impossible to promote. This is mainly because the pigment imitation wax printing has the industry problem of back penetration and pattern clarity. These two properties are the core properties of wax printing fabrics. Without breaking through this industry pain point, pigment imitation wax printing cannot be achieved. Summary of the invention
[0005] Based on this, it is necessary to provide a printing paste and a paint printing paste and their applications to address the above-mentioned problems. The printing paste has excellent shear thinning ability and water holding capacity, so that the paint printing paste with the printing paste can have both back-bleeding effect and pattern clarity during paint printing, thus solving industry problems.
[0006] The invention provides a printing paste for wax-like printing of coatings, which comprises, by mass fraction, 10%-30% of an adhesive, 5.2%-12% of a hand-feel finishing agent, 0.5%-3% of a penetrant, 1%-3% of a pH regulator, 2%-6% of a metal salt, 2%-5% of a composite thickener, 0.3%-0.5% of a defoamer and 40%-78% of water, wherein the composite thickener comprises an alkali swelling thickener and an inverse emulsion thickener.
[0007] In one embodiment, the alkali swelling thickener is selected from at least one of thickener HASE and thickener ASE-60;
[0008] And / or, the inverse emulsion thickener is selected from thickener PTF;
[0009] And / or, the mass ratio of the alkali swelling thickener to the inverse emulsion thickener is 1:1-6:1.
[0010] In one embodiment, the viscosity of the printing paste is 2000mPa·s-8000mPa·s;
[0011] And / or, the pH of the printing paste is 8-9.
[0012] In one embodiment, the hand-feel finishing agent includes polyvinyl acetate-b-acrylate emulsion and cationic film.
[0013] In one embodiment, the mass ratio of the polyvinyl acetate-b-acrylate emulsion to the cationic film is 2.5:1-50:1.
[0014] In one embodiment, the cationic film is selected from polyvinyl alcohol.
[0015] In one embodiment, the penetrant is selected from at least one of penetrant JFC-1 and penetrant JFC-E;
[0016] And / or, the pH adjuster is selected from at least one of liquid alkali, aqueous ammonia, and 2-amino-2-methyl-1-propanol;
[0017] And / or, the metal salt is at least one selected from sodium chloride, potassium chloride, sodium dihydrogen phosphate, magnesium sulfate, and sodium acetate;
[0018] And / or, the defoamer is selected from at least one of a mineral oil defoamer and a silicone defoamer.
[0019] In one embodiment, the adhesive is selected from random polyacrylate RAFT emulsion, and the random polyacrylate RAFT emulsion contains 6%-8% silicone.
[0020] A pigment printing paste comprising the printing paste as described above.
[0021] An application of the above-mentioned pigment printing paste in pigment printing.
[0022] In the printing paste of the present invention, a composite thickener is formed by compounding an alkali swelling thickener with a reverse emulsion thickener, and is compounded with a metal salt for use. On the one hand, the rheological properties of the printing paste can be regulated, so that the printing paste has excellent shear thinning ability, and then the paint printing paste with the printing paste has excellent penetration ability in the process of paint imitation wax printing. On the other hand, the viscosity of the composite thickener can be reduced, so that the amount of the composite thickener can be increased, so that the printing paste has excellent water holding capacity, and then the paint printing paste with the printing paste can ensure the clarity of the pattern during the penetration process of the paint imitation wax printing. Therefore, the paint printing paste with the printing paste can have both back penetration effect and pattern clarity during the paint imitation wax printing, and promote the promotion and use of paint imitation wax printing. DETAILED DESCRIPTION
[0023] For ease of understanding of the present invention, the present invention will be described more fully below with reference to relevant embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0025] The invention provides a printing paste for wax-like printing of coatings, which comprises, by mass fraction, 10%-30% of an adhesive, 5.2%-12% of a hand-feel finishing agent, 0.5%-3% of a penetrant, 1%-3% of a pH regulator, 2%-6% of a metal salt, 2%-5% of a composite thickener, 0.3%-0.5% of a defoamer and 40%-78% of water, wherein the composite thickener comprises an alkali swelling thickener and an inverse emulsion thickener.
[0026] The above-mentioned printing paste is compounded with an alkali swelling thickener and a reverse emulsion thickener to form a composite thickener, and is compounded with a metal salt for use. On the one hand, the rheological properties of the printing paste can be regulated so that the printing paste has excellent shear thinning ability. On the other hand, the viscosity of the composite thickener can be reduced, thereby increasing the dosage of the composite thickener and making the printing paste have excellent water holding capacity.
[0027] Among them, alkali swelling thickeners and inverse emulsion thickeners are both polyacrylic acid thickeners. The difference is that alkali swelling thickeners refer to polyacrylic acid thickeners prepared by normal emulsion polymerization, and inverse emulsion thickeners refer to polyacrylic acid thickeners prepared by inverse emulsion polymerization.
[0028] In one embodiment, the alkali swelling thickener is selected from at least one of thickener HASE and thickener ASE-60, and the inverse emulsion thickener is selected from thickener PTF.
[0029] Preferably, the mass ratio of the alkali swelling thickener to the inverse emulsion thickener is 1:1-6:1, more preferably 2:1-3:1, which is conducive to further controlling the rheological properties of the printing paste.
[0030] In one embodiment, the metal salt is selected from at least one of sodium chloride, potassium chloride, sodium dihydrogen phosphate, magnesium sulfate, and sodium acetate, which is conducive to better synergistic effect with the composite thickener.
[0031] In one embodiment, the hand-feel finishing agent includes polyvinyl acetate-b-acrylate emulsion and cationic film. The hand-feel finishing agent can fully penetrate into the fabric, so that the printed fabric has a unique hand feel and appearance style of thick and fluffy, soft and elastic, and cotton cloth texture, and can save a hand-feel finishing process, improve production efficiency, and reduce sewage discharge.
[0032] It is understood that the polyvinyl acetate-b-acrylate emulsion is a polyvinyl acetate-acrylate emulsion with a block structure, which can be prepared by existing techniques, for example: adding a RAFT agent, an emulsifier, vinyl acetate, hexadecane and deionized water into a reactor and stirring vigorously to form an emulsion, introducing a protective gas after ultrasound, heating to 60°C-75°C, adding an initiator to initiate polymerization, and the reaction time lasts for 2.5h-3h; then uniformly adding acrylic acid ester mixed monomers to the reactor, and controlling the reaction temperature to 1. The addition is completed within 5h-3h, and the reaction temperature during the addition is controlled at 60°C-75°C; after all the addition is completed, the reaction system is kept at 70°C-80°C for 1h-1.5h, and the polyvinyl acetate-b-acrylate emulsion is obtained after cooling to room temperature, wherein the acrylate mixed monomer preferably includes 40wt%-65wt% of acrylate, 20wt%-30wt% of methyl acrylate, 15wt%-28wt% of octadecyl acrylate and 0.5wt%-2wt% of hydroxyethyl acrylate.
[0033] Preferably, the chemical structure of the polyvinyl acetate-b-acrylate emulsion is as shown in formula (1),
[0034]
[0035] Wherein, R1 is selected from methoxy, ethoxy, isopropoxy, tert-butoxy, 4-methoxyphenol, 4-formylphenol or 4-fluorophenol, R2 is selected from hydrogen, methyl, octadecyl or hydroxyethyl, R3 is selected from phenethyl, methylacetoxy, ethylpropionyloxy or diethylmalonyloxy, m and n are both integers, m is 20-300; n is 20-300.
[0036] In one embodiment, the cationic film is selected from polyvinyl alcohol.
[0037] Preferably, the mass ratio of the polyvinyl acetate-b-acrylate emulsion to the cationic film is 2.5:1-50:1, which is beneficial to further improve the feel of the printed fabric.
[0038] In one embodiment, the mass fraction of the penetrant in the printing paste is preferably 0.5%-1%. Specifically, the penetrant is selected from at least one of penetrant JFC-1 and penetrant JFC-E.
[0039] In one embodiment, the defoamer is selected from at least one of a mineral oil defoamer and a silicone defoamer.
[0040] In one embodiment, the pH regulator is selected from at least one of liquid alkali, ammonia water, and 2-amino-2-methyl-1-propanol. The pH regulator can be used to adjust the pH of the printing paste, thereby exerting the rheological properties of the composite thickener.
[0041] Preferably, the pH of the printing paste is 8-9, which is conducive to further exerting the rheological properties of the composite thickener.
[0042] In one embodiment, the adhesive is selected from random polyacrylate RAFT emulsion, and the random polyacrylate RAFT emulsion contains 6%-8% silicone. The color depth of the coating is improved in the printing stage through the deepening effect of silicone, and has good hand feel and color fastness.
[0043] In one embodiment, the raw materials for preparing the adhesive include, by mass fraction: 20%-30% of acrylate, 3%-8% of styrene, 3%-8% of acrylonitrile, 1%-5% of N-n-butoxymethyl acrylamide, 1%-3% of hydroxyethyl acrylate, 3%-10% of vinyl silicone oil, 0.1%-2% of amphiphilic macromolecular RAFT agent, 0.5%-2% of alkali, 0.05%-0.15% of initiator, 0.1%-0.5% of zinc oxide, 40%-50% of deionized water, and 3%-5% of blocked isocyanate crosslinking agent.
[0044] It should be noted that the preparation method of the adhesive includes: blending deionized water, an amphiphilic macromolecular RAFT emulsifier and N-n-butoxymethyl acrylamide, stirring evenly, as an aqueous phase; blending acrylate, styrene, acrylonitrile, hydroxyethyl acrylate, vinyl silicone oil and zinc oxide as an oil phase; under the action of a high-speed shear emulsifier, adding the oil phase to the aqueous phase for pre-emulsification, and then emulsifying it with an ultrasonic homogenizer, and then transferring the pre-emulsion to a four-necked flask, heating it to 60°C-80°C, first introducing a protective gas, and then adding part of the initiator aqueous solution to initiate the reaction; after the temperature stabilizes at 80°C, slowly adding an alkali aqueous solution in batches, and then keeping warm; after the insulation is completed, adding the remaining initiator aqueous solution and continuing the reaction; after the reaction is completed, cooling to room temperature, adding a blocked isocyanate cross-linking agent, stirring evenly, and filtering to obtain the adhesive.
[0045] In one embodiment, the viscosity of the printing paste can be adjusted according to different processes. In one embodiment, the viscosity of the printing paste is 2000mPa·s-8000mPa·s, and more preferably 5000mPa·s-6000mPa·s.
[0046] The present invention also provides a method for preparing the printing paste as described above, comprising the following steps:
[0047] S1, mixing an adhesive, a hand finishing agent, a penetrant, a pH adjuster and water to obtain a mixed solution;
[0048] S2, placing a metal salt, an alkali swelling thickener and an inverse emulsion thickener in a mixed solution, adding a defoaming agent after mixing, and obtaining a printing paste.
[0049] In step S1, when the hand finishing agent includes a soft film, in order to better dissolve the soft film, in one embodiment, the soft film is prepared into an aqueous solution, dissolved at a temperature of 75° C.-85° C., cooled, and then mixed with other components.
[0050] In step S2, in order to better adjust the viscosity of the printing paste, in one embodiment, the metal salt is first placed in a mixed solution and stirred before adding a thickener. Since the thickener has the property of reducing viscosity when encountering salt, the viscosity of the added thickener can be reduced, thereby allowing the thickener to be better mixed with other components.
[0051] The present invention also provides a paint printing paste including the printing paste as described above. Since the printing paste has excellent shear thinning ability and excellent water holding capacity, the paint printing paste has excellent penetration ability during paint printing and can ensure the clarity of the pattern, thereby having both back penetration effect and pattern clarity, which can promote the promotion and use of paint printing.
[0052] The present invention also provides an application of the above-mentioned paint printing paste in paint imitation wax printing, which can solve the problem of difficulty in balancing back bleeding and pattern clarity in the paint printing process. When printed on coarse cotton fabric, a printed fabric can be obtained with consistent color on both sides, excellent pattern clarity, and a hand feel style close to that of active imitation wax printed fabric.
[0053] The printing paste and the coating printing paste and their application will be further described below by the following specific examples. However, it will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0054] The adhesives used in the following Examples 1-8 and Comparative Examples 1-4 are prepared by the following preparation method: 0.5g of ammonium persulfate and 0.5g of sodium bisulfite are dissolved in 20g of deionized water to obtain an initiator aqueous solution. 245g of deionized water, 10g of macromolecular RAFT emulsifier and 8g of N-n-butoxymethyl acrylamide are added to a reactor and stirred to mix as an aqueous phase. 108g of butyl acrylate, 18g of styrene, 18g of acrylonitrile, 6g of hydroxyethyl acrylate, 35g of vinyl silicone oil (V401-1000) and 1g of nano zinc oxide are added to a beaker and stirred evenly as an oil phase. Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the aqueous phase for pre-emulsification, and then ultrasonically dispersed with an ultrasonic homogenizer to obtain an emulsion. The ultrasonically dispersed emulsion is then transferred to a four-necked flask, nitrogen is passed for 30min, the temperature is raised to 65°C, 5 / 6 of an aqueous solution of ammonium persulfate and sodium bisulfite is added, and the reaction is initiated. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15min, and then keep warm for 4h. After the insulation is completed, add the remaining aqueous solution of ammonium persulfate and sodium bisulfite, and continue the reaction for 0.5h. After the reaction is completed, cool to room temperature, add 25g of blocked isocyanate crosslinking agent, stir evenly, filter the material to obtain adhesive A, the silicone content of which is 7%. Adhesive B used in Example 9 is also prepared by this preparation method, except that the silicone content of this adhesive B is 8%.
[0055] The polyvinyl acetate-b-acrylate emulsions used in the following Examples 1-9 and Comparative Examples 1-4 were prepared by the following preparation method: by mass fraction, 2.0% ethyl (methoxy) propionyloxy dithioester RAFT agent, 3% emulsifier isomeric alcohol polyoxyethylene ether and secondary alcohol polyoxyethylene ether, 18% vinyl acetate, 0.6% hexadecane and 48.32% deionized water were added to the reactor and stirred vigorously to form an emulsion, and nitrogen was passed through for 30 minutes after ultrasonication for 2 minutes, and the temperature was raised to 75°C, and 0.08% potassium persulfate initiator was added to initiate polymerization, and the reaction time lasted for 3 hours until the reflux was completed. Then 28% of the acrylate mixed monomer oil phase (wherein each monomer component was: 61.5% acrylate, 18% methyl acrylate, 20% octadecyl acrylate, 0.5% hydroxyethyl acrylate) was uniformly added to the reactor, and the addition was completed within 2.5 hours, and the reaction temperature during the addition was controlled at 70°C. After all the addition was completed, the reaction system was kept at 70° C. for 1 h, and then cooled to room temperature to obtain a polyvinyl acetate-b-acrylate emulsion.
[0056] Example 1
[0057] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0058] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 20% of adhesive A, 57.7% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.4% of thickener ASE and 1.2% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0059] Example 2
[0060] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0061] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 20% of adhesive A, 53.8% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 6% of sodium chloride was added and stirred until completely dissolved. Then, 3.6% of thickener ASE and 1.8% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0062] Example 3
[0063] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0064] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 10% of adhesive A, 67.2% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.6% of thickener ASE and 1.4% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0065] Example 4
[0066] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0067] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 30% of adhesive A, 48% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.2% of thickener ASE and 1% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0068] Example 5
[0069] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0070] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 30% of adhesive A, 50.5% of deionized water, 5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.2% of thickener ASE and 1% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0071] Example 6
[0072] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0073] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 30% of adhesive A, 45.5% of deionized water, 10% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.2% of thickener ASE and 1% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0074] Example 7
[0075] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0076] In terms of mass fraction, 10% of the above-mentioned film aqueous solution, 30% of adhesive A, 42.8% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.2% of thickener ASE and 1.2% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0077] Example 8
[0078] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0079] In terms of mass fraction, 15% of the above-mentioned film aqueous solution, 30% of adhesive A, 37.7% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed. After stirring evenly, 4% of sodium chloride was added and stirred until completely dissolved. Then, 2.2% of thickener ASE and 1.3% of thickener PTF were slowly added, the slurry viscosity was adjusted to 5000 mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0080] Example 9
[0081] The difference between Example 9 and Example 1 is that an equal amount of adhesive B is used to prepare the printing paste, wherein the paste viscosity is 5000 mPa·s.
[0082] Comparative Example 1
[0083] Comparative Example 1 was carried out with reference to Example 1, except that only thickener ASE was used and the slurry viscosity was adjusted to 5000 mPa·s.
[0084] Comparative Example 2
[0085] Comparative Example 2 was carried out with reference to Example 1, except that only thickener PTF was used and the slurry viscosity was adjusted to 5000 mPa·s.
[0086] Comparative Example 3
[0087] Comparative Example 3 was carried out with reference to Example 1, except that an equal amount of ammonium chloride was used instead of sodium chloride.
[0088] Comparative Example 4
[0089] The polyvinyl alcohol was mixed with water, heated to 80°C, stirred until completely dissolved, and cooled to 25°C to obtain a film aqueous solution with a mass fraction of 10%.
[0090] In terms of mass fraction, 5% of the above-mentioned film aqueous solution, 20% of adhesive A, 61.8% of deionized water, 7.5% of polyvinyl acetate-b-acrylate emulsion, 1% of penetrant TF-107D, and 1% of 2-amino-2-methyl-1-propanol were mixed and stirred at high speed, and then 1% of thickener ASE and 0.5% of thickener PTF were slowly added to adjust the slurry viscosity to 5000mPa·s, and 0.3% of mineral oil defoamer was added to obtain a printing paste.
[0091] The printing pastes obtained in Examples 1-9 and Comparative Examples 1-4 were tested for back penetration rate, pattern clarity, color depth, thickness, and fluffiness. The test methods are as follows. The test results are shown in Table 1.
[0092] (1) Back penetration rate and color depth: After adding the printing paste to the coating color paste, the printed fabric is printed. The K / S value of the front and back of the printed fabric is measured using a spectrophotometer, where K is the colorant absorption coefficient and S is the colorant scattering coefficient. The back penetration rate is the ratio of the K / S value on the back of the printed fabric to the K / S value on the front of the printed fabric; the color depth is the K / S value on the front of the printed fabric.
[0093] (2) Pattern clarity: Add coating to the printing paste to prepare printing color paste, immerse the fabric sample in the printing color paste, and measure the climbing height of the color paste in 5 minutes. The lower the climbing height, the better the pattern clarity.
[0094] (3) Fabric thickness and fluffiness: The apparent thickness of the fabric was measured using the FAST-1 compressible fabric style meter. The calculation formula is: T0 = T2 - T 100 ; Where: T0 is the apparent thickness (mm); T2 is 2cN / cm 2 Lower fabric thickness (mm); T 100 100cN / cm 2 Lower fabric thickness (mm); Fluffiness: 1-5, the larger the number, the fluffier; Thickness: 1-5, the larger the number, the thicker.
[0095] Table 1
[0096]
[0097] Note: Ratings range from 1 to 5, with 1 being the worst and 5 being the best.
[0098] According to Table 1, it can be seen from Examples 1, 3, and 4 that an increase in the amount of printing adhesive used will lead to a decrease in back permeability, an increase in color depth, a thicker feel, and a decrease in fluffiness. In order to obtain a deeper color depth, the preferred amount of paint printing adhesive is 30%, and the feel is adjusted on this basis. According to the results of Examples 4-6, it is found that the amount of polyvinyl acetate-b-acrylate emulsion is preferably 6%-8%. Further increasing the amount will not continue to thicken but will lead to a significant decrease in fluffiness. According to Examples 4, 7, and 8, it can be seen that cationic film will affect back permeability and the thickness of the fabric, and the appropriate amount is preferably 0.8%-1.2%. The results show that the embodiments provided in this patent can basically meet the performance requirements of imitation wax printing, and the obtained printed fabric has consistent front and back sides, good pattern clarity, deep and bright colors, and a thick and fluffy feel.
[0099] It can be seen from Example 1 and Comparative Examples 1-2 that the use of alkali swelling thickener or reverse thickener alone cannot simultaneously meet the requirements of back permeability and pattern clarity. It can be seen from Example 1 and Comparative Example 3 that the effect of organic salt is slightly worse than that of metal salt.
[0100] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A printing paste for coating wax-like printing, characterized in that: The invention comprises, by mass fraction, 10%-30% of an adhesive, 5.2%-12% of a hand finishing agent, 0.5%-3% of a penetrant, 1%-3% of a pH regulator, 2%-6% of a metal salt, 2%-5% of a composite thickener, 0.3%-0.5% of a defoaming agent and 40%-78% of water, wherein the composite thickener comprises an alkali swelling thickener and an inverse emulsion thickener.
2. The printing paste according to claim 1, characterized in that The alkali swelling thickener is selected from at least one of thickener HASE and thickener ASE-60; And / or, the inverse emulsion thickener is selected from thickener PTF; And / or, the mass ratio of the alkali swelling thickener to the inverse emulsion thickener is 1:1-6:
1.
3. The printing paste according to claim 1 or 2, characterized in that The viscosity of the printing paste is 2000mPa·s-8000mPa·s; And / or, the pH of the printing paste is 8-9.
4. The printing paste according to claim 1 or 2, characterized in that The hand-feel finishing agent comprises polyvinyl acetate-b-acrylate emulsion and cationic soft film.
5. The printing paste according to claim 4, characterized in that The mass ratio of the polyvinyl acetate-b-acrylate emulsion to the cationic film is 2.5:1-50:
1.
6. The printing paste according to claim 5, characterized in that The cationic film is selected from polyvinyl alcohol.
7. The printing paste according to claim 1 or 2, characterized in that The penetrant is selected from at least one of penetrant JFC-1 and penetrant JFC-E; And / or, the pH adjuster is selected from at least one of liquid alkali, aqueous ammonia, and 2-amino-2-methyl-1-propanol; And / or, the metal salt is at least one selected from sodium chloride, potassium chloride, sodium dihydrogen phosphate, magnesium sulfate, and sodium acetate; And / or, the defoamer is selected from at least one of a mineral oil defoamer and a silicone defoamer.
8. The printing paste according to claim 1 or 2, characterized in that The adhesive is selected from random polyacrylate RAFT emulsion, and the random polyacrylate RAFT emulsion contains 6%-8% of silicone.
9. A pigment printing paste comprising the printing paste according to any one of claims 1 to 8.
10. Use of the pigment printing paste as claimed in claim 9 in pigment imitation wax printing.